An Optimization Model Applied to Active Solar Energy System for Buildings in Cold Plateau Area. (June 2016) - Si, Pengfei; Lv, Yuexia; Liu, Xichen; Rong, Xiangyang; Feng, Ya
Abstract: The large-scale utilization of solar energy in buildings is one of the most promising technologies to solve the global energy shortage problem and reduce the carbon dioxide emissions. The present paper has proposed an optimization model coupled with solar thermal and photovoltaic systems. Optimization results of active solar energy system from the energy saving view and economical view have been obtained for typical hotel and office buildings in cold plateau area, respectively.